2016
DOI: 10.1213/ane.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnographic Observational Study to Evaluate and Optimize the Use of Respiratory Acoustic Monitoring in Children Receiving Postoperative Opioid Infusions

Abstract: In this study, the use of RR monitoring did not improve the detection of respiratory depression. An RR threshold, which would have been predictive of desaturations, would have resulted in an unacceptably high false alarm rate. Future research using a combination of variables (e.g., SpO2 and RR), or the measurement of tidal volumes, may be needed to improve patient safety in the postoperative ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous study that the use of acoustic respiratory monitoring in children receiving opioid infusions on a postsurgical ward was evaluated and false alarm was assessed was reported [9].This report indicated that, episodes of desaturation were observed in 9 patients, but the use of acoustic respiratory monitoring did not improve the detection of respiratory depression. And this reported that acoustic monitor resulted in an unacceptably high false alarm rate.…”
Section: False Alarmmentioning
confidence: 96%
“…Previous study that the use of acoustic respiratory monitoring in children receiving opioid infusions on a postsurgical ward was evaluated and false alarm was assessed was reported [9].This report indicated that, episodes of desaturation were observed in 9 patients, but the use of acoustic respiratory monitoring did not improve the detection of respiratory depression. And this reported that acoustic monitor resulted in an unacceptably high false alarm rate.…”
Section: False Alarmmentioning
confidence: 96%